2008
DOI: 10.1029/2007jd008986
|View full text |Cite
|
Sign up to set email alerts
|

MST radar and radiosonde observations of inertia‐gravity wave climatology over tropical stations: Source mechanisms

Abstract: [1] In this paper, possible source mechanisms for the generation of inertia-gravity wave activity over a tropical station, Gadanki (13.5°N, 79.2°E), are investigated using a long-term data set obtained from Indian mesosphere-stratosphere-troposphere (MST) radar. The gravity wave analysis is carried out in two different height regions, namely, 4-14 and 17-21 km, representing the troposphere and lower stratosphere, respectively. Clear seasonal variation in the wave activity has been noticed in both regions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 33 publications
10
58
0
Order By: Relevance
“…A clear annual oscillation can be noticed in both zonal and meridional velocities. Similar variations are also observed by the MST radar located at the same site in between 4 and 20 km (Ratnam et al, 2008;Basha and Ratnam, 2009;Debashis Nath et al, 2009). …”
Section: Background Meteorological Conditions Obtained During the Balsupporting
confidence: 68%
“…A clear annual oscillation can be noticed in both zonal and meridional velocities. Similar variations are also observed by the MST radar located at the same site in between 4 and 20 km (Ratnam et al, 2008;Basha and Ratnam, 2009;Debashis Nath et al, 2009). …”
Section: Background Meteorological Conditions Obtained During the Balsupporting
confidence: 68%
“…A clear annual oscillation can be noticed in both zonal and meridional velocities. Similar variations are also observed by the MST radar located at the same site between 4 and 20 km (Venkat Ratnam et al, 2008;Basha and Ratnam, 2013;Nath et al, 2009). Monthly mean OLR around Gadanki at 17:30 LT is shown in Fig.…”
Section: Background Meteorological Conditionssupporting
confidence: 65%
“…Further, as it assumes monochromatic waves, it is not always applicable in the real atmosphere. Notwithstanding this limitation, with this method, convection and vertical shear have been identified as the possible sources of the observed medium and low-frequency GWs in the troposphere and lower stratosphere over many places (e.g., Venkat Ratnam et al, 2008). It becomes difficult to apply this method for GWs that are observed in the mesosphere and lower thermosphere (MLT) region, where simultaneous measurements of temperatures (with wind) would not be available.…”
Section: Introductionmentioning
confidence: 99%
“…Over the Indian region, several studies (Venkat Ratnam et al, 2008, and references therein) have been carried out for extracting GW parameters using various instruments (MST radar, radiosondes, lidar and satellite observations). In a few studies (Kumar, 2006(Kumar, , 2007Dhaka et al, 2002;Venkat Ratnam et al, 2008;Debashis Nath et al, 2009;Dutta et al, 2009;Leena et al, 2012a, b), possible sources in the troposphere for their generation are identified which include convection, wind shear and topography.…”
Section: Introductionmentioning
confidence: 99%